Wave propagation in a transversely isotropic porous ocean bottom. Issue 8 (13th September 2020) - Teymouri, Hamid; Khojasteh, Ali; Rahimian, Mohammad; Pak, Ronald Y. S.
Abstract: The equations of wave motion are considered in this article for three-layered medium which consists of liquid and porous layers with finite depth and solid half-space such as ocean bed. By virtue of scalar potential functions for each layer, complicated differential equations of layers are reduced to ordinary differential equations. An analytical method is applied to determine the Green's functions of media based on an arbitrary shaped time-harmonic excitation at the interface of liquid and porous layers. A Mathcad code is provided to compute the complex integrals. Displacement and stress fields of three layers are discussed. Comparing with special cases, existing answers represent the validity of the proposed method. Numerical results are carried out for circular patch, ring and point loads, and the effects of various parameters on the behavior of the system are plotted. Finally, the achieved results were under discussion.